Nano/micrometer porous conductive network structure Li4Ti5O12@C/CNT microspheres with enhanced sodium-storage capability as an anode material. Issue 41 (21st September 2022) - Zhu, Guozhen; Yu, Linhe; Yang, Qihao; Che, Renchao
Abstract : Li4 Ti5 O12 @C/CNT microspheres were prepared by a facile spray drying method, which exhibited long cycling stability (85.45 mA h g −1 after 500 cycles at 500 mA g −1 ) and excellent rate capability (61.16 mA h g −1 after 10 cycles at 1000 mA g −1 ). Abstract : Li4 Ti5 O12 @C/CNT microspheres, wherein CNTs were firmly anchored to Li4 Ti5 O12 @C nanoparticles, were prepared via a facile spray drying method and subsequently annealed in an argon atmosphere, exhibiting long cycling stability (charge/discharge capacities of 85.45/86.18 mA h g −1 after 500 cycles at 500 mA g −1 ) and excellent rate capability (charge capacity of 61.16 mA h g −1 after 10 cycles at 1000 mA g −1 ). The special spherical structure design is not only beneficial to improving the structural stability and reaction kinetics of the electrode materials during the long-term extraction–insertion of sodium ions but also supplies numerous interfacial sites to store more sodium ions.